2018
DOI: 10.1016/j.jth.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

The public bicycle-sharing scheme in Brisbane, Australia: Evaluating the influence of its introduction on changes in time spent cycling amongst a middle- and older-age population

Abstract: This is a repository copy of The public bicycle-sharing scheme in Brisbane, Australia: Evaluating the influence of its introduction on changes in time spent cycling amongst a middle-and older-age population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The improvement of walking and cycling infrastructure had no effect on the overall level of PA, but it attracted more users and had a positive effect on active transportation in more than half of the studies. These findings are in line with previous reviews [ 9 , 11 , 32 ]. These types of interventions seem to be promising for promoting active travel.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The improvement of walking and cycling infrastructure had no effect on the overall level of PA, but it attracted more users and had a positive effect on active transportation in more than half of the studies. These findings are in line with previous reviews [ 9 , 11 , 32 ]. These types of interventions seem to be promising for promoting active travel.…”
Section: Discussionsupporting
confidence: 94%
“…In one study, the level of PA even decreased after installation of a new trail [ 27 ]. However, five studies [ 28 32 ] reported that the level of walking and/or cycling increased after built environment interventions and three studies [ 33 – 35 ] reported an increasing number of users of new facilities. The availability of public transport had a significantly positive effect on PA [ 36 ] and walking [ 28 , 30 , 31 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies identified that males and younger populations account for a larger percentage of docked bike-sharing users (e.g. Fuller et al, 2011;Heinen, Kamruzzaman, & Turrell, 2018;Heinen, van Wee, & Maat, 2010). Studies on docked bike-sharing systems in Beijing, Shanghai and Hangzhou also revealed that docked bike-sharing users have higher levels of car ownership than non-users (Fishman et al, 2013).…”
Section: Existing Research On Docked Bike-sharing Systemsmentioning
confidence: 98%
“…Much research has been devoted to the question of who uses BSS. In general, reflecting cycle usage overall, BSS users appear to be younger adults, have higher incomes than average, male and are more likely to own a bicycle (Fishman et al, 2013; Heinen et al, 2018;Ogilvie and Goodman, 2012;Soltani et al, 2019;Zhao et al, 2019). These socio-economic characteristics may seem similar to those that are generally linked to cycling (see e.g.…”
Section: Determinants Of Cycle Hire Scheme Usage 211 Who Uses Cycle H...mentioning
confidence: 99%